Pogledi na preprečevanje kriminalitete v pozno modernih družbah - Meško, Gorazd (Teorija in praksa, 2000)
The paper presents some latest views on crime prevention and its accompanying dilemmas. The author contemplates on the dimensions and concepts of crime prevention, at the same time presenting its role and significance, not forgetting the role that the state and politics play in its clarification. Crime prevention, as a new paradigm in social control, is discussed upon and its background presented. Some attempts on the classification of crime prevention are also put before us.
Keywords: kriminaliteta; preprečevanje kriminalitete; postmoderna družba; družbeno nadzorstvo